Claudin 18.2 is a target for IMAB362 antibody in pancreatic neoplasms. Issue 3 (16th September 2013) - Wöll, Stefan; Schlitter, Anna Melissa; Dhaene, Karl; Roller, Marc; Esposito, Irene; Sahin, Ugur; Türeci, Özlem
<x xml:space="preserve">Abstract</x> The majority of pancreatic neoplasms are characterized by a generally lethal progress within a short period of time after primary diagnosis and the mortality of patients is expected to increase further. Due to lack of efficient screening programs and moderate response to treatments, novel compounds for treatment are needed. We investigated the CLDN18.2 expression in affected patients as in vitro feasibility study for a potential treatment with the novel antibody IMAB362. Therefore, we analyzed the expression of CLDN18.2 in normal pancreatic tissues (N = 24), primary lesions (N = 202), metastases (N = 84) and intra‐individually matched samples (N = 48) of patients with pancreatic ductal adenocarcinoma (PDAC), neuroendocrine neoplasia (NEN) and acinar cell carcinoma. A standardized method for evaluation by immunohistochemistry was developed. The specific staining was evaluated by two independent raters and analysis of staining intensities (range 0–3+) and relative proportions of tumor cells were performed. One hundred three (59.2%) samples of primary PDAC were found positive. The vast majority of positive samples were characterized to highly express CLDN18.2: 54.6% (N = 95) with staining intensities of ≥2+. NEN were positive in 20% of cases (all ≥2+). Metastases of pancreatic neoplasms were also frequently found positive with comparable high rates (69.4% of lymph node and 65.7% of liver metastases). The rate of CLDN18.2 positivity is high in pancreatic neoplasms whereby the expression is not limited to the primaries but is also maintained upon metastasis. Thus, a considerable number of patients with pancreatic neoplasms would be in principle eligible for a CLDN18.2‐targeting approach.